KEPUNAN AND MALET OF BANGKA IN THE PERSPECTIVE OF CULTURE INTERPRETATION - Purwanto, Tinggal; Rifa'i, Andi Arif (Journal of Contemporary Islam and Muslim Societies, 2020)
Abstract: This study is an attempt to unveil the meaning as well the function of kepunan and malet  culture in Bangka society with a Qur’anic exegeses perspective. This research begins by examining the meaning of both (kepunan and mallet) and how they function according to the understanding of the Bangka community. In the second stage, this study will interpret the kepunan and malet with the cultural interpretation approach. With this cultural interpretation paradigm, the kepunan which is generally understood by the Bangka community as customs, myths, and syirk (an act and belief of polytheism), even considered as the cause of disaster is eventually interpreted as a form of social solidarity of the people of Bangka. While malet which is understood by the Bangka community as a form and means of rejection of disaster and bad things, could be understood as a form of social ethics of the Bangka community in respecting the gifts of others.  Keywords: kepunan, malet, cultural interpretations